SEJARAH KERAJAAN TURKI UTHMANIYAH DAN SUMBANGANNYA DALAM BIDANG SOSIOPOLITIK ABAD KE-14 HINGGA ABAD KE-20 (History of the Ottoman Empire and Its Contributions in Sociopolitical Aspects from 14th Century Until 20th Century) - Haris, Abu Hanifah (Journal of Al-Tamaddun, 2020)
The Ottoman Empire is an Islamic caliphate that once existed in the Anatolian region of Turkey, whose capital is Istanbul. The Empire is dated from the beginning of the late 13th century until its peak in the 15th and 16th centuries. The Ottoman Empire is also regarded as the Islamic caliphate that succeeded the Abbasid Caliphate, which was overthrown in the 13th century. The Ottoman Empire thereafter became the patron and guardian of the Muslims around the world. This article aims to discuss the history of the Ottoman Empire and its political and social contributions. The scope of the study is from the establisment of the empire in the early 14th century in 1300 until its downfall in the early 20th century (1924). A qualitative approach by means of library research methodology was adopted by referring to various primary sources, such as files and documents like Foreign Office (FO) file obtained from The National Archive, London, and newspapers such as The Singapore Free Press and Mercantile Advertiser and The Straits Times, in addition to secondary sources, such as books, articles, and theses. The study has found that the Ottoman Empire massively contributed to the political and social fields, particularly in the first two centuries of its establishment (in the late 13th century) until the late 16th century.